PENGARUH PROFITBILITAS, LIKUIDITAS, DAN STRUKTUR MODAL TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI BARANG KONSUMSI YANG TERDAFDAT DI BURSA EFEK INDONESIA TAHUN 2019-2021 - Santi Kurnia Rahayuning Tyas; Muhammad Hasan Ma’ruf; Suprihati Suprihati (JURNAL WIRANOMIKA, 2025)
The purpose of this study was to determine the effect of profitability, liquidity, and capital structure on firm value. The population in this study are all issuers which are manufacturing companies in the consumer goods industry sector that are listed on the Indonesia Stock Exchange in 2019 – 2021. The sampling technique used the purposive sampling method so that 66 samples were obtained. The type of research used is quantitative research using secondary data. The analysis technique used in this study uses multiple regression analysis. The results of this study indicate that profitability has a positive effect on firm value, liquidity has a negative effect on firm value, and capital structure has a positive effect on firm value. Keywords : Firm Value, Profitability, Liquidity, Capital Structure